Caracteres fisiológicos e bioquímicos da tolerância à salinidade em clones de cajueiro anão precoce - Pizarro, Juan Carlos Alvarez (2006)
Early-dwarf cashew seedlings (Anacardium occidentale L.) were used in order to investigate the physiological and biochemical changes induced by salt stress. The seeds (nuts) were sown in plastics pots containing vermiculite moistened with either distilled water (control treatment) or NaCl solutions at 8 and 16 dS.m-1 of electrical conductivity (saline treatment), and kept in greenhouse throughout the experimental period. Uniform 28-day-old seedlings were used for the analyses. The first experiment aimed to select, among five clones (CCP 06, CCP 09, CCP 76, Embrapa 51 and BRS 189), the ones showing contrasting salt-tolerance. The effect of salinity on the growth, gas exchange, water content, leaf succulence, osmotic potential and inorganic (Na+, Cl-, K+) and organic (proline, soluble carbohydrates, quaternary ammonium compounds) solute concentration for both salt-sensitive and salt-tolerant clones was studied. Salinity inhibited the growth of all clones studied, being the inhibitory effect on shoot growth more conspicuous than in root growth. Clone CCP 06 leaf area was the most inhibited by salt stress, while clones BRS 189 and CCP 09 leaf areas were the least affected by salinity. Salt stress caused a great decrease in the cotyledon reserve mobilization especially at 16 dS.m-1. Growth reduction was correlated to the reduction in net photosynthetic rate. CCP 06 and BRS 189 showed the greatest and the lowest reduction in photosynthetic rate at 8 dS.m-1, respectively. Although, salinity reduced stomatal conductance, this reduction was not followed by changes in CO2 internal concentration. The water status, expressed as water content in relation to dry mass, was not changed by salt-stress. Salinity induced the lowering of osmotic potential both in leaves and roots of all clones studied. This osmotic adjustment might have lead to turgor maintenance of those tissues. The concentrations of Cl- and Na+ increased with increasing salt stress. Clones BRS 189 and CCP 09 accumulated more Na+ in the roots, and this could explain their efficiency in maintaining a lower ion concentration in shoots, i.e. they regulated more efficiently the transport of Na+ from roots to shoots. The regulation of Cl- transport to shoots was more efficient in clone CCP 09 than in the others. Salinity did not induce significant changes in leaves and stems K+ concentration, but it induced a reduction of K+ concentration in roots. Salinity also induced increases of quaternary ammonium compounds and proline concentration in BRS 189 root at 8 dS.m-1. In addition, this level of salinity increased soluble carbohydrates in the root sap especially in clones BRS 189 and CCP 06. During the second experiment, the effect of salt stress (NaCl at 8 dS.m-1) on the activity of H+-ATPase, lipid composition and peroxidation of root plasma membrane of both salt-tolerant (BRS 189) and salt- sensitive (CCP 06) clones were studied. The vanadate-sensitive H+-ATPase activity was studied in plasma membrane-enriched vesicles isolated by discontinuous sucrose gradient centrifugation from roots. ATP hidrolizing activity in this fraction was mostly inhibited by vanadate and scarcely, by azide and molybdate, indicating that it was essentially enriched in plasma membrane vesicles. Salinity induced a 1.3-fold increase in the H+-ATPase specific activity in roots of BRS 189 seedlings. Salinity had no appreciable effect on the hydrolytic activity of this enzyme during the growth of CCP 06 seedlings. Likewise, clone BRS 189 roots plasma membrane showed higher sterol content and lower phospholipids/total sterol ratio than clone CCP 06. Both properties could contribute to the decrease in Na+ influx or increase in Na+ efflux or “exclusion” from roots. This could result in less Na+ being transported to the shoot, and thus explaining the higher salt-tolerance of clone BRS 189. The higher degree of root plasma membrane lipid peroxidation of clone, and the lower proline and ammonium quaternary compounds contents of CCP 06 when compared to BRS 189 could also explain the differences in salt-tolerance between the two clones. These organic solutes could protect and stabilize plasma membrane against oxidative stress. Phosphatidylglycerol (PG), phosphatidylethanolamine (PE) and phosphatidylserine (PS) were the major phospholipids in the plasma membrane from BRS 189 roots. Salinity induced increases in the relative proportions of PE and phosphatidylinositol (PI), while PG and PA were reduced. No changes were detected in PS in relation to control plant. The importance of lipid composition changes on H+-ATPase activity must be more studied.